Role of scatter factor in the pathogenesis of AIDS-related Kaposi sarcoma. - Naidu, Y M (1994)
Kaposi sarcoma (KS) is a complex multicellular neoplasm that is commonly associated with AIDS. The pathogenesis of KS is not well understood. KS tumor cells grow poorly in vitro and require medium conditioned by retrovirus-infected T lymphocytes. We observed that conditioned medium (CM) from type II human T-cell leukemia virus (HTLV-II)-infected T cells (HTLV-II CM) induces conversion of endothelial cells (ECs) to a KS tumor cell-like phenotype. ECs grown in HTLV-II CM acquired a spindle-shaped morphology, the ability to express factor XIIIa and other KS cell markers, and a cytokine production profile similar to that of KS cells. We found that HTLV-II CM contains large quantities of scatter factor (SF), an angiogenic cytokine that stimulates cell motility. SF induced ECs to become spindle-shaped and express factor XIIIa. Moreover, SF was found to be a mitogen for KS cells in vitro and was identified within KS lesions in vivo. SF mRNA was present in KS cells in vitro, and antibodies against SF inhibited the growth of KS cells. The receptor for SF, the c-met protein, was expressed by ECs, dermal dendrocytes, and KS tumor cells in vitro and in vivo. HTLV-II CM was highly angiogenic in vivo, which was blocked by antibodies against SF. Based on these findings, we suggest that SF plays a role in the initiation and maintenance of KS lesions.